1993
DOI: 10.1002/lary.5541030404
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve morbidity following parotid surgery for benign disease: The cleveland clinic foundation experience

Abstract: Standard surgical management for benign tumors of the parotid gland requires either superficial, subtotal, or total parotidectomy with preservation of the facial nerve. Although this approach is effective in minimizing recurrence, the resultant facial nerve morbidity is seldom addressed. Two hundred fifty‐six consecutive patients who underwent parotid surgery for benign neoplasia at this institution in the past 15 years are reviewed, with attention to postoperative facial nerve function. Immediate dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
93
2
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 7 publications
11
93
2
5
Order By: Relevance
“…The incidence of transient facial nerve palsy was 68.26% in our study, higher than studies reported by Laccorreye [15] & Mehle [16]. Permanent facial nerve palsy was seen in 0.04% of our patients.…”
Section: Images In Surgerycontrasting
confidence: 61%
“…The incidence of transient facial nerve palsy was 68.26% in our study, higher than studies reported by Laccorreye [15] & Mehle [16]. Permanent facial nerve palsy was seen in 0.04% of our patients.…”
Section: Images In Surgerycontrasting
confidence: 61%
“…14 In another study it was mentioned that most of the patients with post operative facial nerve paresis, regained their normal function within 12-14 months after surgery, regardless of the pathology and that a slower recovery occurred for up to two years after surgery. 15 In this study, majority of patients showed significant functional recovery within three months after the surgery and all recovery occurred within six months after surgery.…”
Section: Discussionmentioning
confidence: 52%
“…Permanent facial nerve dysfunction is reported in 0-4 % of cases following facial nerve dissection procedures [45][46][47]. A meta-analysis showed twice the chance of permanent facial nerve dysfunction with ECD compared with superficial parotidetomy and a three times higher chance following total parotidectomy compared to superficial parotidectomy [1].…”
Section: Permanent Facial Nerve Dysfunctionmentioning
confidence: 99%